Biocompatibility of anionic collagen matrices and its influence on the orientation of cellular growth. - Buchaim, Rogério L.; Goissis, Gilberto; Andreo, Jesus Carlos; Roque, Domingos D.; Roque, José S.; Buchaim, Daniela V.; Rodrigues, Antonio C. (Brazilian Dental Science, 2010)
This study aimed to analyze the biocompatibility of anionic collagen matrices, the local bone response following implantation in surgically-created bone defects, and also the influence of the collagen fiber orientation on the neoformed osseous tissue. Seventy two rats (Rattus norvegicus albinus) were used in this experiment. The animals were divided into four experimental groups: Group 1 (control), without implants; Group 2, pericardium medullar implants 12 hours; Group 3, medullar implants of tendon 24 hours, with the long axis of collagen fibers oriented parallel to the long axis of the tibia; and Group 4, medullar implants of tendon 24 hours, with the long axis of collagen fibers perpendicular to the long axis of the tibia. After the experimental surgery, the evolution of the repair process was microscopically evaluated at 7, 15, and 30 days post-surgery. The results demonstrated that the mplanted matrices are biocompatible and act as a scaffold inducing bone formation, mainly in the Group 4 animals. At first, cellularity follows the arrangement of collagen fibers, later obtaining a multidirectional growth.